2005
DOI: 10.1177/0022487104272056
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Learner Advantages on Teachers' Beliefs About Critical-Thinking Activities

Abstract: To investigate teachers' beliefs about critical-thinking (CT) activities for different populations of learners, the Critical Thinking Belief Appraisal (CTBA) was administered to 145 practicing secondary teachers. Teachers rated both high-CT and low-CT activities as more effective for highadvantage learners than low-advantage ones, demonstrating strong “advantage effects.” They also rated high-CT activities as more effective than low-CT ones for both high-advantage and lowadvantage learners, demonstrating “peda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 34 publications
2
38
0
5
Order By: Relevance
“…This belief may become a self-fulfilling prophecy, because teachers would tend to avoid the use of higher order thinking activities with LA students who would be "stuck" at learning that emphasizes memorization and methods of drill and practice. A more recent study (Warburton and Torff 2005) similarly demonstrated that teachers rated both high and low critical thinking activities as more effective for high-advantaged learners than for lowadvantaged learners. Since at least one of the reasons for such beliefs is teachers' feeling that they lack satisfactory instructional means for teaching thinking to students with low academic achievements (Zohar et al 2001), it is imperative to develop such instructional means and assess their effects for LA students.…”
Section: Theoretical Backgroundmentioning
confidence: 89%
See 1 more Smart Citation
“…This belief may become a self-fulfilling prophecy, because teachers would tend to avoid the use of higher order thinking activities with LA students who would be "stuck" at learning that emphasizes memorization and methods of drill and practice. A more recent study (Warburton and Torff 2005) similarly demonstrated that teachers rated both high and low critical thinking activities as more effective for high-advantaged learners than for lowadvantaged learners. Since at least one of the reasons for such beliefs is teachers' feeling that they lack satisfactory instructional means for teaching thinking to students with low academic achievements (Zohar et al 2001), it is imperative to develop such instructional means and assess their effects for LA students.…”
Section: Theoretical Backgroundmentioning
confidence: 89%
“…First, it carries a clear recommendation stating that it is indeed valuable to apply explicit instruction of MSK for teaching thinking to LA students. Second, as explained earlier, teachers often do not believe that instruction of higher order thinking is an appropriate educational goal for LA students (Zohar et al 2001;Raudenbush et al 1993;Warburton and Torff 2005). One common reason for this conviction relates to a lack of satisfactory instructional means for teaching thinking to LA students.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As exemplifi ed below, only four of the papers (El-Dib, 2007 ;Freese, 2006 ;Leonard, Brooks, Barnes-Johnson, & Berry, 2010 ;Warburton & Torff, 2005 ) provided explicit defi nitions of the concept. Many of the discussions related to the works of infl uential US teacher education researchers, such as Darling-Hammond, Shulman, and Cochran-Smith, and their arguments for critical thinking were underpinned by the notion that it was part of effective teaching to increase students' learning outcomes (Darling-Hammond, 2010 ;Goodman, Arbona, & Dominguez de Rameriz, 2008 ;Leonard et al, 2010 ).…”
Section: Critical Thinking In Teacher Education: Three Different Meanmentioning
confidence: 99%
“…An illustration of this is the argument that all learners should have equal access to instructions that encourage them to think critically. For instance, Warburton and Torff ( 2005 ) claim that all learners should participate in 'high' critical thinking activities, such as classroom conversations, journals, reaction papers and portfolios. El-Dib ( 2007 , p. 25) argues that critical thinking starts in refl ection 'as the process by which teachers engage in aspects of critical thinking such as careful deliberation and analysis, making choices'.…”
Section: Critical Thinking In Teacher Education: Three Different Meanmentioning
confidence: 99%
“…Thus, in order to improve student learning, understanding and thinking skills, schools of education should first equip student teachers with the necessary knowledge and skills to properly educate their own students when they start teaching. Hence, as Warburton (2008) suggested, the pre-service education training period is an ideal time to carry out interventions that promote effective teaching through challenging and redirecting student teachers' own misconceptions to achieve the desired outcomes.…”
Section: Introductionmentioning
confidence: 99%